Community Empowerment in MSME Craft Production Based on Conventional Method and Innovation with 3D Printing - Yetrina , Mutiara; Fatchurrohman, Nanang; Farid , Mohammad; Apri Pratama, Dian (Majalah Ilmiah UPI YPTK, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economic growth of Padang City, particularly in the handicraft sector, which represents both cultural identity and a vital source of local economic activity. However, technological limitations and low production efficiency remain major obstacles to improving the competitiveness of local crafts in the global market. This Community Service Program (PkM) aims to integrate 3D printing technology with conventional production methods as an effort to enhance product quality, efficiency, and design innovation. The implementation method includes identifying the potential and challenges faced by artisans, conducting training on the use of 3D printing, and providing mentoring in the design and production processes. This approach combines the artistic touch and craftsmanship of conventional manual techniques with the precision and speed of digital technology. The results show an improvement in artisans’ ability to utilize digital technology for prototyping and developing new designs that are more responsive to market trends. Furthermore, the training and equipment facilitation support continuous knowledge transfer, strengthening the innovation capacity and independence of MSMEs. The combination of traditional skills and modern technology not only produces products with high aesthetic value but also opens opportunities for market expansion and increased economic value. Therefore, the application of 3D printing has proven to be an effective innovative solution for enhancing the competitiveness and sustainability of the local handicraft sector in the era of the digital creative industry.